Bone Remodeling: Theranostic Bioabsorbable Bone Fixation Plate with Drug‐Layered Double Hydroxide Nanohybrids (Adv. Healthcare Mater. 21/2016). Issue 21 (9th November 2016) - Kim, Myung Hun; Hur, Woojune; Choi, Goeun; Min, Hye Sook; Choi, Tae Hyun; Choy, Young Bin; Choy, Jin‐Ho
Abstract : Choy and his team demonstrate a novel strategy for precise theranostic bone repair on page 2765. A theranostic layer is made of a composite of risedronate‐layer double hydroxide (RSLDH) nanohybrids and biodegradable polymer (poly(lactic‐ co ‐glycolic acid)), in which both radiopacity (diagnostic) and risedronate delivery (therapeutic) could be controlled upon changing the layer property. A combined entity of the theranostic layer and biodegradable, orthopedic fixation device allows for post‐surgery diagnosis and expedited bone repair in in vivo cranial defect animal models.